The Effect of Compensation and Motivation on Employee performance - Dodi Agusra; Liga Febrina; Erfa Okta Lussianda; Aznur Rizki Susanti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2021)
The purpose of this study was to determine the effect of compensation and motivation on employee performance at PT Adicitra Mulyatama in Pekanbaru. Riau Indonesia. The sample for this study was 40 people, sampling using the census sampling technique. The results of this study state that compensation has a significant effect on employee performance. Motivation affects employee performance and compensation and motivation affects employee performance with a contribution of 80.4% to employee performance while the remaining 19.6% is influenced by other variables not examined in this research.